Demographics and Sociocultural Factors and Attitudes Affecting Patients’ Usage of Complementary Medicine in a South Indian Cancer Hospital - Sanaka, Krishna Om; Siddiqui, Mohamed T.; Rajappa, Senthil; Hadley, Craig (Indian Journal of Integrative Medicine, 2025)
Background: Complementary and alternative medicine (CAM) is widely used by cancer patients and is embedded in Indian culture. Objectives: We investigated the usage patterns and attitudes towards CAM in South Indian cancer patients as they were understudied. Methods: We interviewed consecutive patients undergoing outpatient cancer treatment at a specialized charity hospital in a large South Indian city and obtained information. Results: A total of 101 patients (mean age 55.4  13.1 years and fema female gender 73.3%) were enrolled, and CAM use was reported by 51 (50.5%) patients. CAM users were more likely to be uninsured (49% vs. 30%), illiterate, or college-educated (29.4% vs. 12%), and less likely to use tobacco (3.9% vs. 20%) or alcohol (2% vs. 12%) (p < 0.05 for all). Most users expressed satisfaction with CAM (25% very satisfied and 66.7% somewhat satisfied), and CAM non-users expressed not knowing about these methods (58%) or not believing in their efficacy (46%). Around 57% of CAM users did not discuss their usage with their physicians. Conclusions: Overall, CAM usage was common and influenced by social factors in South Indian patients. Therefore, physicians should take the initiative to inquire about patients’ use of CAM, which has potential implications for treatment.